Impact of industrial effluents on geotechnical properties of soil. (2021) - Vinoth, S.; Rajeshkumar, V.; Sivabalan, T.; Surya, M.; Thamilkumaran, M.; Saiprakash, S.
Abstract: The paper discuss the study on contaminants of the effluents from the industries affect the soil's physical and engineering properties. Hence the soil properties are to be enhanced for strengthening of soil for the constructional and other activities. In metropolitan areas and highly populated cities the volume of pollutants produced by industries like dyeing, tanneries etc were enormously high. The chemical and physical properties very highly affected by those pollutants which make the soil unfit for any activity. In this study dyeing industry waste is taken as pollutants and laboratory experiments are carried out to determine soil properties. Physical properties like natural moisture content (NMC), Specific gravity (Sg), grain-size distribution (Gsd), Constant head permeability (CHP) are performed for both polluted and conventional soil samples. Engineering properties such as shear strength and permeability characteristics are taken. Comparison was made for both the samples and presented. The polluted soil contains 30% increase in manganese, 9.1% increase in copper content, 2% increase in lead and 10% increase in iron. Industrial effluents have affected the soil of about 11.9% in shear strength, from non-polluted soil which is been collected. Industrial effluents have affected the soil and an decrement of about 76.1% in permeability.